2006
DOI: 10.1182/blood-2005-08-3412
|View full text |Cite
|
Sign up to set email alerts
|

Human thymus contains multipotent progenitors with T/B lymphoid, myeloid, and erythroid lineage potential

Abstract: It is a longstanding question which bone marrow-derived cell seeds the thymus and to what level this cell is committed to the T-cell lineage. We sought to elucidate this issue by examining gene expression, lineage potential, and self-renewal capacity of the 2 most immature subsets in the human thymus, namely CD34 ؉ CD1a ؊ and CD34 ؉ CD1a ؉ thymocytes. DNA microarrays revealed the presence of several myeloid and erythroid transcripts in CD34 ؉ CD1a ؊ thymocytes but not in CD34 ؉ CD1a ؉ thymocytes. Lineage poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 42 publications
7
100
0
3
Order By: Relevance
“…In addition to their T-cell differentiation potential, fetal CD34 hi CD1a À thymocytes possess strong NKcell potential, as well as B-and dendritic cell potential, but lack granulocyte/macrophage potential. 32 Weerkamp et al recently showed that the adult CD34 þ CD1a À thymocyte subset has differentiation potential not only for B, NK and dendritic cells, but also for myeloid and erythroid lineages, 33 leading to the hypothesis that the adult human thymus is seeded by a multipotent stem cell-like progenitor instead of a CLP. Still, the multilineage differentiation capacity of both fetal and adult early thymocytes remains to be shown at the single cell level, thus the possibility exists that, analogously to the corresponding murine DN1 thymocyte stage (CD44 þ CD25 À ), 34 the human CD34 þ CD1a À thymic subset is heterogeneous and contains multiple progenitors with different differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their T-cell differentiation potential, fetal CD34 hi CD1a À thymocytes possess strong NKcell potential, as well as B-and dendritic cell potential, but lack granulocyte/macrophage potential. 32 Weerkamp et al recently showed that the adult CD34 þ CD1a À thymocyte subset has differentiation potential not only for B, NK and dendritic cells, but also for myeloid and erythroid lineages, 33 leading to the hypothesis that the adult human thymus is seeded by a multipotent stem cell-like progenitor instead of a CLP. Still, the multilineage differentiation capacity of both fetal and adult early thymocytes remains to be shown at the single cell level, thus the possibility exists that, analogously to the corresponding murine DN1 thymocyte stage (CD44 þ CD25 À ), 34 the human CD34 þ CD1a À thymic subset is heterogeneous and contains multiple progenitors with different differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…The exact nature of the progenitors is unclear, but some level of multipotency is now commonly accepted. 6,7 Development into a mature T cell comprises the ordered rearrangement of the different TCR genes and positive and negative selection events that finally lead to the expression of mature TCRab and TCRgd molecules recognizing non-self peptides in context of self-major histocompatibility complex (MHC) or equivalent molecules. These processes take place during a series of discrete phenotypic stages that can be recognized by expression of several key membrane molecules, most notably CD4 and CD8 (Figure 1a).…”
Section: Overview Of T-cell Development In the Thymusmentioning
confidence: 99%
“…-/ -cells transplanted, T cells increased to normal or near-normal levels, consistent with the selective advantage of the T-cell lineage in these mice and BMindependent homing in the thymus (Weerkamp et al, 2006). In contrast, B-cell reconstitution was strongly dependent on conditioning.…”
Section: Discussionmentioning
confidence: 58%
“…The donor HSCs and B-cell progenitors may have engrafted poorly in the BM because of the limited accessibility of occupied HSC niches. The relative advantage in reconstitution and marking of T-cell progenitors might be attributed to the higher selective advantage of these cell types, the lack of competing T-cell progenitor cells in the host (Buckley, 2004), or the ability of multipotent progenitors T cells to home directly to the thymus (Weerkamp et al, 2006). Recently initiated gene therapy trials to treat SCID-X1 with self-inactivating (SIN) gammaretroviral vectors adhere to similar protocols without preconditioning (Mukherjee and Thrasher, 2013).…”
mentioning
confidence: 99%